Using Special Physical Education Curriculum-Based Measurement to Improve Student Motor Development in Both General and Special Needs Population: Review of Early Research Lasting More than Five Decades - Popović, Miloš (Innovare Journal of Education, 2024)
The main goal of this study is to acquaint experts in the field of education with the results of early research, which are related to the problems they face even now when it comes to sensitive groups with special needs. Previous experiences can be a good indicator of different models of action for pedagogues and managers within the modern education system. Inclusive education has become a reality faced by all participants in the process. Effective action models have been adopted in developed countries, primarily Western countries. However, in less developed countries, it is evident that the problem of inclusion is faced later, primarily due to legal regulations and the need for more funds for specific training of all participants. This issue is especially neglected when it comes to inclusion in the physical education of children with various disorders in motor development. Examples from practice in earlier research can be a good guide for overcoming various obstacles that all participants face today, both in special and inclusive physical education. Controversies are still occurring between supporters of the traditional particular education approach versus the modern, inclusive education model. A better familiarity with the issue can contribute to overcoming prejudices, which this overview study of earlier research can contribute.